Kuersetin dari Daun Erythrina poeppigiana (leguminosae) - Herlina, Tati; Supratman, Unang (Jurnal Natur Indonesia, 2016)
Erythrina plants known plants “dadap” is a higher plant that grows in tropical and subtropical regions. E. poeppigiana plants was a source of secondary metabolites, which contain flavonoids. This study aims to isolate the flavonoid compounds from the leaves of  E. poeppigiana through the stages of extraction, fraction, separation and purification. E. poeppigiana leaves powder (2.5 kg) was extracted with methanol and partitioned with n-hexane and ethyl acetate. Furthermore, the separation of ethyl acetate of E. poeppigiana leaves fraction using a combination of column chromatographic was obtained pure compound (5 mg) in the form of a yellow amorphous  solid. The chemical structure of pure compound was based on the data spectroscopy (MS, UV, IR, 1H-NMR and 13C-NMR) and identified as the compound 3,3 ‘, 4’, 5,7-pentahidroksiflavon or known as quercetin.